1997
DOI: 10.1086/514846
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Mutations in the Batten Disease Gene, CLN3

Abstract: Batten disease (juvenile-onset neuronal ceroid lipofuscinosis [JNCL]) is an autosomal recessive condition characterized by accumulation of lipopigments (lipofuscin and ceroid) in neurons and other cell types. The Batten disease gene, CLN3, was recently isolated, and four disease-causing mutations were identified, including a 1.02-kb deletion that is present in the majority of patients (The International Batten Disease Consortium 1995). One hundred eighty-eight unrelated patients with JNCL were screened in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 17 publications
2
129
2
Order By: Relevance
“…There are ten missense mutations in CLN3 (see, http://www.ucl.ac.uk/ncl) that change conserved amino acid residues, most of which cause classic JNCL disease. However, some result in an altered disease course (Munroe et al, 1997) suggesting that the mutant protein retains some residual function. We first examined the location of three GFP-Btn1 proteins carrying different missense mutations 3 hours after repression of their expression in btn1⌬ cells.…”
Section: The Human Cln3 Gene Can Functionally Compensate For Btn1mentioning
confidence: 99%
“…There are ten missense mutations in CLN3 (see, http://www.ucl.ac.uk/ncl) that change conserved amino acid residues, most of which cause classic JNCL disease. However, some result in an altered disease course (Munroe et al, 1997) suggesting that the mutant protein retains some residual function. We first examined the location of three GFP-Btn1 proteins carrying different missense mutations 3 hours after repression of their expression in btn1⌬ cells.…”
Section: The Human Cln3 Gene Can Functionally Compensate For Btn1mentioning
confidence: 99%
“…To date, >40 different mutations in CLN3 have been described (summarized in a mutation database: http://www.ucl.ac.uk/ ncl/cln3.shtml). CLN3 disease is recessive, and 85% of CLN3 patients carry a 1-kb deletion that causes the loss of exons 7 and 8 (5). Although the CLN3 protein is well conserved from yeast to humans, its function is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 In a large study, Munroe et al 6 found that 74% of 188 unrelated affected individuals from 18 different countries were homozygous for this mutation, and a further 22% were compound heterozygotes for the deletion and another mutation. Thus, a test for only the CLN3 1-kbp deletion in a patient with some suspicion of BD would give either a diagnosis (homozygous result) or raise the level of suspicion (heterozygous result) in over 90% of patients who actually do have this disease.…”
Section: Discussionmentioning
confidence: 99%
“…With no other known high frequency CLN3 mutations, further molecular diagnosis of BD requires a variety of methods including mutation scanning and sequencing for micromutations and Southern blots for large deletions. 6,11,12 The absence of the CLN3 1-kbp deletion in a patient with some suspicion of BD might also prompt further consideration of other diagnoses. is the opposite of that seen when using a dual probe fluorescence resonance energy transfer system to generate the fluorescent signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation